Socio Pedagogical Study â€œReligiusity Power Therapyâ€ Drug Victims (Therapeutic Model Design At Drug Rehabilitation Islamic Boarding Schools) - Subiyantoro, Subiyantoro; Hidayati, Wiji; Setyaningsih, Rini; Sholikhin, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Narcotics, Alcohol, Psychotropics and Addictive Substances (NAPZA) are the causes of human anxiety disorders, a psychological, pedagogical and physical disorder that affects an individual's existence in social life. The presence of Islamic boarding schools is a forum for rehabilitating drug users spiritually which affects their spiritual and physical health. The purpose of this research is to find an effective drug rehabilitation model design through a religious approach in Islamic boarding schools as reference for policy makers in implementing the drug rehabilitation model. This research was conducted at Ar-Rahman Islamic Boarding School Palembang, Tetirah Dzikir Islamic Boarding School Yogyakarta, Al-Islamy Kulon Progo Islamic Boarding School, Hafara Yogyakarta Rehabilitation Institution, Ainul Yakin Gunung Kidul Islamic Boarding School, and Utsman Bin Affan Qur'anic Healing Riau Islamic Boarding School which implements the concept of a rehabilitation Islamic boarding school with religious power in it. The research method used is descriptive qualitative. The data sources used consist of primary data sources through in-depth interviews with managers of rehabilitation Islamic boarding schools, National Narcotics Agency, victims of drug users, communities around Islamic boarding schools. Secondary data sources are in the form of guidelines for the management of drug rehabilitation Islamic boarding schools and reports on the rehabilitation process. The data analysis technique refers to the concept of Miles and Huberman with the stages of domain analysis, tacsonomic analysis, componential analysis, discovery cultural themes. The results of this study indicate that religiosity power therapy is proven to be able to rehabilitate drug users through the stages of activities in it in the form of qur'anic healing, verbal-careful-deed dhikr, night prayers, congregational prayers, safar, pilgrimages, bathing in repentance, spiritual rituals, seminars and religious motivation. The sociopedagogical form of religiosity power therapy model practiced in these six Islamic boarding schools starts from the initial acceptance which includes registration, rapid test, urine test and service orientation of the intake program. Then proceed with the program orientation with detoxification or stabilization, exercise, rest, and health checks. In the next stage, the patient can join the program, namely joining the rehabilitation program from community therapy, spiritual therapy, psychological therapy, social therapy, and medical therapy. Or after the toxification is complete, you can also choose another alternative, namely outpatient care. The program then underwent a recognition period and program re-entry by providing skills, both soft skills and hard skills. And the last is the complete program determined by the counselor to be able to go home. Theoretically-practically, the results of this study contribute to the importance of collaborative therapeutic practice between medical, religious-practice, and pedagogical for drug victims. For policy makers, it can be considered as a way of providing moral and material support to educational institutions/drug rehabilitation institutes, so that these community institutions can function more in solving drug-related problems.